2011
DOI: 10.1002/rra.1393
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analyzing flow diversion in branching channels with symmetric geometry

Abstract: This paper aims at the investigation and analysis of numerical and laboratory modelling of flow in branched channels with symmetrical geometry and varying hydraulic conditions. Details of velocity and water-level profiles in branching locations are discussed. In some low-slop regions like plains, rivers may be branching; or in alluvial plains where the slop is low, meanders may appear. On the other hand, in the mountainous and semi-mountainous areas with relatively steep slops, arterial rivers can be formed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Depending of the development of river, water quality may vary with the presence of a dam for example, reducing both sediments transportation and fauna distribution of derived zooplankton (Takao et al, 2008). River branching related to watershed topography, and its consequences on flowrate (Yousefi and Ghiassi, 2011) can also be considered local factor of water quality variation. Finally, floods frequency increase is a strong factor of water quality variation with pollutants and solids transportation and modification of flow routing (He et al, 2007).…”
Section: Hydrological Limits For Monitoring Relevancementioning
confidence: 99%
“…Depending of the development of river, water quality may vary with the presence of a dam for example, reducing both sediments transportation and fauna distribution of derived zooplankton (Takao et al, 2008). River branching related to watershed topography, and its consequences on flowrate (Yousefi and Ghiassi, 2011) can also be considered local factor of water quality variation. Finally, floods frequency increase is a strong factor of water quality variation with pollutants and solids transportation and modification of flow routing (He et al, 2007).…”
Section: Hydrological Limits For Monitoring Relevancementioning
confidence: 99%
“…Other applications of one-dimensional open-channel flow models include longterm simulations [16], river network modeling [10], flood predictions and similar hydraulic engineering problems. Despite the fact that these models are widespread, their proper calibration still presents a major challenge [8,9,25]. Castellarin et al [3] discussed useful guidelines for identification of the geometric description of natural rivers [3].…”
Section: Introductionmentioning
confidence: 99%
“…These hydrodynamic phenomena affect withdrawal efficacy. They are closely related to the withdrawal conditions (He et al 2021b) and water intake structure parameters (Yousefi et al 2010;Shen et al 2020), such as the intake width depth ratio, withdrawal angle, intake type and water diversion ratio. Effects of bank slope on the flow patterns in river intakes were studied, and it was found that the inclining bank causes the bottom stream tube width to be greater than at the surface (Seyedian et al 2014).…”
Section: Introductionmentioning
confidence: 99%